SCREENING OF MICROORGANISMS ISOLATED FROM PETROLEUM OIL CONTAMINATED SOIL FOR VEGETABLE OIL CONVERSION TO BIO-DIESEL - V.NARASIMHAN; B.VALENTIN BHIMBA (International Journal of Pharma and Bio Sciences, 2015)
Decreasing fossil fuel stocks has prompted research and development to find alternatives, particularly from renewable energy resources. Lower alcohol, fatty ester called as Bio-Diesel production using vegetable oils with the help of biological catalysts (Lipases) is being considered as one such good alternative. Soil samples in and around petroleum stock processing plant wereused to isolate fungal species. Fungal species were purified on PDA agar plates and tested for their relative ability to hydrolyze glycerides. The stain that showing high level of lipase activity on Tween 80, Rhodamine-B and Phenol red containing agar plates was selected and characterized. Three differently colored and fast growing fungal colonies were observed, isolated, purified and tested for their relative lipolytic activity. Black colored fungal colony was observed to have highest lipase activity in both tween-80 and Rhodamine-B agar plates for fatty ester and olive oil. The sample was found to be Aspergillus niger strain, resembling closely WHAK1 18S ribosomal RNA gene. The nucleotide sequence is annotated with NCBI accession no. KR261667